2021
DOI: 10.17582/journal.pjar/2021/34.3.462.472
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of PB Ropes (Synthetic Sex Pheromone) against Pink Bollworm, Pectinophora gossypiella (Saunders) (Lepidoptera: Gelichidae), Destructive Cotton Pest, in different Ecological Zones of Punjab, Pakistan

Abstract: C otton has vital role in economy of Pakistan. It is main source of fiber as well as vegetable oil. It is major source of foreign exchange obtained by exporting raw cotton to many countries of world. Cotton production and area is continuously reducing in Pakistan due to biotic and abiotic stresses and competition from other crops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…As the larva bores inside the boll, the lint is cut and tied, resulting in a significant loss of cotton quality. The pest completes four generations on cotton crop and the fifth-generation rests on the left-over bolls on the cotton sticks and the bolls in the ginning factories (Hussain et al, 2021). Unlu and Bilgic (2004) reported that 1% increase in the infestation rate of PBW caused a 2.5-6.0% yield loss of cotton.…”
Section: Introductionmentioning
confidence: 99%
“…As the larva bores inside the boll, the lint is cut and tied, resulting in a significant loss of cotton quality. The pest completes four generations on cotton crop and the fifth-generation rests on the left-over bolls on the cotton sticks and the bolls in the ginning factories (Hussain et al, 2021). Unlu and Bilgic (2004) reported that 1% increase in the infestation rate of PBW caused a 2.5-6.0% yield loss of cotton.…”
Section: Introductionmentioning
confidence: 99%
“…As the larva bores inside the boll, the lint is cut and tied, resulting in a significant loss of cotton quality. Four generations completes its development on the cotton crop and the fifth generation rests on the leftover bolls on the cotton sticks and the bolls in the ginning factories (Hussain et al, 2021). Under dry conditions, the number of larvae in the bolls is directly related to the loss in the yield and quality of the produce.…”
Section: Introductionmentioning
confidence: 99%